2017
DOI: 10.1002/ijc.30805
|View full text |Cite
|
Sign up to set email alerts
|

What has preoperative radio(chemo)therapy brought to localized rectal cancer patients in terms of perioperative and long‐term outcomes over the past decades? A systematic review and meta‐analysis based on 41,121 patients

Abstract: We asked what preoperative radiotherapy/chemoradiotherapy (PRT/PCRT) has brought to patients in terms of perioperative and long-term outcomes over the past decades. A systematic review and meta-analysis was conducted using PubMed, Embase and Web of Science databases. All original comparative studies published in English that were related to PRT/PCRT and surgical resection and which analyzed survival, postoperative and quality of life outcomes were included. Data synthesis and statistical analysis were carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
1
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 47 publications
4
65
1
2
Order By: Relevance
“…Pre-operative chemoradiotherapy (CRT), followed by total mesorectal excision, is the standard of care for patients with locally advanced rectal cancer (LARC) (2)(3)(4). The combination of radiation with capecitabine has been shown to significantly improve local control and local recurrence-free survival, but does not improve metastasis-free survival or overall survival (5). To acquire better outcomes, researchers have attempted to identify novel radiosensitizers, such as oxaliplatin, irinotecan and some molecular targeting agents (6).…”
Section: Introductionmentioning
confidence: 99%
“…Pre-operative chemoradiotherapy (CRT), followed by total mesorectal excision, is the standard of care for patients with locally advanced rectal cancer (LARC) (2)(3)(4). The combination of radiation with capecitabine has been shown to significantly improve local control and local recurrence-free survival, but does not improve metastasis-free survival or overall survival (5). To acquire better outcomes, researchers have attempted to identify novel radiosensitizers, such as oxaliplatin, irinotecan and some molecular targeting agents (6).…”
Section: Introductionmentioning
confidence: 99%
“…The multidisciplinary approach including radiotherapy, chemotherapy, and surgery is regarded as the standard of care for locally advanced (T3/4 and/or node positive) mid-to-low rectal cancer patients [ 1 , 2 ]. Neoadjuvant regimens consisting of preoperative long-course 5‑FU (5‑fluorouracil) based chemoradiotherapy (CRT; 45–50.4 Gy, 25–28 fractions) and preoperative short-course radiotherapy (25 Gy, five fractions) are considered the primary treatments of choice [ 3 5 ]. The CAO/ARO/AIO-94 trial demonstrated the superiority of preoperative CRT with respect to local control, treatment compliance, and overall toxicity profile, but not in overall survival benefit, when compared to postoperative CRT [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Irradiation before surgical resection sterilizes gross and microscopic tumor cells under the better condition of tumor oxygenation, suggesting potential benefits in preventing further tumor spread within the locoregional RT field 5 , 9 . In clinics, main reasons for the recommendation have been derived from some favorable oncologic outcomes: down-staging effect, increased likelihood of sphincter preservation, and relatively better treatment compliance expected 6 , 7 , 9 11 . In this study, the unadjusted results indicating better survival with preoperative RT might be attributable to favorable factors related to the use of RT prior to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, preoperative use of RT has become the preferred option for locally advanced rectal adenocarcinomas 6 . Given that the Dutch trials demonstrated improved local control with neoadjuvant RT 7 , 8 , three phase III randomized controlled trials, including the German CAO/ARO/AIO-94, National Surgical Adjuvant Breast and Bowel Project (NSABP) R-03, and a Korean study, compared pre- and postoperative use of RT 9 11 .…”
Section: Introductionmentioning
confidence: 99%